Gorky rises - Steig, William, 1907-2003. (New York : Farrar, Straus, Giroux, 1980)
Clutching the bottle of magic potion he has made, a young frog falls asleep and wakes to find himself floating in the sky.
Keywords: Magic -- Fiction; Frogs -- Juvenile fiction; Animals -- Fiction